Review of Nadège Ragaru, “Et les Juifs bulgares furent sauvés…” Une histoire des savoirs sur la Shoah en Bulgarie - Benveniste, Henriette-Rika (Historein, 2022)
Review of Nadège Ragaru, “Et les Juifs bulgares furent sauvés…” Une histoire des savoirs sur la Shoah en Bulgarie. Paris: Sciences Po Les Presses, 2020. 382 pp. To view the full text, click on the button "HTML".